Mesenteric Pseudocyst Following Blunt Abdominal Trauma: Report of a Case and Review of Literature - Gjinoska, Kaludia; Kostovski, Ognen; Nikolovski, Andrej; Bajdevska Dukovska, Daniela; Alimi, Agron; Antovikj, Svetozar (Fortune Journals, 2022)
Mesenteric pseudocysts are rare intraabdominal lesions. A total of 29 similar case reports were retrieved via the Medline/PubMed search engine. They represent a subtype of mesenteric cysts displaying histological similarity to pancreatic pseudocysts which are usually surrounded by a thick fibrous wall without an inner epithelial lining. Mesenteric pseudocysts may present as any other expanding intraabdominal lesion. Accurate preoperative characterization of mesenteric cystic lesions remains challenging. Imaging diagnostics for most of the cases involve both ultrasound and computerized tomography. It is unclear whether routine MRI use would increase preoperative diagnostic accuracy and aid in preoperative planning. Total surgical excision of the pseudocyst has been the treatment of choice. Surgical removal has been achieved by means of open surgery, laparoscopy and the robotic system. It remains unclear to this date whether other treatment approaches are feasible. Other options such as debridement, marsupialization or partial excision have been considered inadequate due to concerns such as the possibility of malignant cell seeding, septic complications and risk of recurrence. We present the case of a posttraumatic mesenteric pseudocyst following blunt abdominal trauma in a 27 year old female, treated by surgical excision
Keywords: Mesenteric cyst; Mesenteric pseudocyst; Blunt abdominal trauma